PEMBUATAN STAND KELISTRIKAN SISTEM MIRROR KACA SPION PADA MOBIL - Pujiono, Akhmad (Surya Teknika : Jurnal Ilmiah Teknik Mesin, 2018)
ABSTRACT This final project aims to find anything what mirror electrical system components and how the electrical system of mirrors. The components I use different brands allowing the trouble of having to manually search for the terminal itself may even be improved so that these components can be applied in an electrical system, switch mirror used to use switch-owned Daihatsu xenia and rearview mirrors using mirror-owned suzuki APV. Electric current from the batteries in order not to standardize through fuse surge occurs when a short-circuit. In making the stand carried out gradually from the beginning to the welding welding end, to painting and installation of components required in the manufacture of electrical stand this mirror. Tests performed after all the electrical components mounted on a stand assembled using wired and assembled one by one, requiring 10 red wire and cable 2 negative / black. Keywords : Stand, mirrors and electrical components